Financial Performance and the Effect on Sustainability Reports Disclosure, Company Size, and Solvency - Kartini, Endang (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The company has the goal of getting profits, by having profits it will be easier to carry out its operational activities. Companies that are very effective and efficient in carrying out their operational activities must have good financial performance. This research was conducted with the aim of knowing and analyzing the effect of disclosure of sustainability reports, company size and solvency on the company's financial performance. To answer the objectives of this study requires a quantitative method, the sample used in this study is a company listed on the SRI-Kehati index on the Indonesia Stock Exchange which consists of 13 companies. Determination of the sample in this study using the technique purposive sampling. The data analysis used is multiple regression analysis of panel data. The proxy used for the company's financial performance in this study is Return on Assets (ROAs). The results of this study indicate that disclosure sustainability reports, company size and solvency companies simultaneously have a significant influence on the company's financial performance.